A pharmacological profile of propoxazepam — a new antiepileptic substance - Golovenko, N.Ya.; Andronati, S.A.; Larionov, V.B.; Reder А.S. (Reports of the National Academy of Sciences of Ukraine, 2018)
The analysis of the dose-effect pharmacological action for propoxazepam on the models of chemically and electrically induced seizures is carried out. The peculiarities of the compound influence on the different genesis seizures manifestations and their redistribution are determined. Pharmacological indices (therapeutic index, wideness, interval, and safety factor) have been calculated, which characterize the efficacy and safety of propoxazepam. The data presented suggest that the future use of propoxazepam as an antiepileptic agent is more secure in those pathologies that are more relevant to the GABA- and glycine-ergic mechanisms.